Studi Literatur : Faktor-faktor yang Mempengaruhi Penghindaran Pajak pada Perusahaan Perdagangan di Indonesia - Dinar Nurhaliza; Vera Aprilda Rizki; Nabilla Eka Indriyani; Puspita Kusumawati; Novi Khoiriawati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research is a literature study that aims to identify and analyze the elements that influence tax avoidance practices in trading sector companies. Tax avoidance is a strategy taken by companies to minimize the tax burden that must be paid. Although legal, it often raises ethical debates and has an impact on the country's foreign exchange earnings. The research method used in this study is a literature review of various scientific journals and relevant publications that discuss the determinants of tax avoidance, especially in the trade sector. This research takes data from various sources that have been indexed by SINTA. Researchers searched for all relevant data until it was classified into nine relevant sources and discussed in this study. The following factors that affect tax avoidance include leverage on tax avoidance, profitability on tax avoidance, and company size on tax avoidance. The results of the study indicate that leverage, profitability, and company size affect the practice of tax avoidance. This study provides insight for stakeholders, such as the government and investors, in understanding the characteristics of companies that tend to practice tax avoidance, as well as a basis for formulating more effective tax policies.